2014
DOI: 10.1186/s40200-014-0108-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome in patients with minor beta thalassemia and its related factors: a cross-sectional study

Abstract: BackgroundAtherosclerotic disorders, hypertension and lipid profile alterations are of a lower prevalence in patients with minor beta thalassemia. On the other hand, nowadays, metabolic syndrome is considered as one of the major risk factors of developing cardiovascular diseases. Therefore, the present study was performed to determine the prevalence of metabolic syndrome in patients with minor beta thalassemia.MethodsIn this case-control study, body length, weight and waist circumference, blood pressure, fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…The selection flow chart is shown in Figure 1. Of the included studies, seven studies [30, 33, 34, 36, 39, 40, 43] were from Italy; seven studies [14, 16, 18, 20, 21, 31, 42] were from Iran; five studies [17, 19, 27, 44, 45] were from Egypt; five studies [4, 8, 22, 23, 35] were from the China region, including the mainland [22], Hong Kong [23], and Taiwan [4, 8, 35]; three studies [11, 12, 32] were from India; two studies [41, 47] were from Arabia; one study [37] was from Germany. The other studies were from Australia [26], Brazil [3], France [9], Lebanon [41], Oman [15], Turkey [25, 38], the United Kingdom [46], and the United States of America [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection flow chart is shown in Figure 1. Of the included studies, seven studies [30, 33, 34, 36, 39, 40, 43] were from Italy; seven studies [14, 16, 18, 20, 21, 31, 42] were from Iran; five studies [17, 19, 27, 44, 45] were from Egypt; five studies [4, 8, 22, 23, 35] were from the China region, including the mainland [22], Hong Kong [23], and Taiwan [4, 8, 35]; three studies [11, 12, 32] were from India; two studies [41, 47] were from Arabia; one study [37] was from Germany. The other studies were from Australia [26], Brazil [3], France [9], Lebanon [41], Oman [15], Turkey [25, 38], the United Kingdom [46], and the United States of America [2].…”
Section: Resultsmentioning
confidence: 99%
“…Thalassemia has long-term extravascular hemolysis which increases iron absorption in the intestinal tract and decreases the bioavailability of iron. This phenomenon coupled with long-term multiple blood transfusions could lead to iron overload and increase the amount of iron ions [31, 32]. The most frequent endocrine disorders were abnormal glucose metabolism, hypogonadotropic hypogonadism, hypothyroidism, and hypoparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some studies that have explored the coexistence of metabolic syndrome in patients with thalassemia minor and it has been suggested that the prevalence of metabolic syndrome showed no relationship with sex and age and these patients had just higher BMI [23]. It has also been reported that patients with thalassemia minor have a better lipidemic and metabolic profile; however, women seem to be at least equally protected against cardiovascular risk compared with men [24].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that chronic microcytic erythrocytic hemolysis in BTM patients leads to oxidative stress and liver inflammation, which then lead to insulin resistance (12,14) . Gozashti et al noted BTM is associated with high prevalence of carbohydrate-related metabolic disorders which result liver inflammation and subsequent insulin resistance (15) . On the other hand, Gozashti and colleagues ATP-related data indicated that the prevalence of metabolic syndrome in thalassemia patients was below that of the normal population (16.7% vs 36.7%).…”
Section: Discussionmentioning
confidence: 99%